(untitled) (Applied Biological Research, 2019)
Obesity-related kidney diseases require an effective approach to avert high fat-diet induced renal damage through oxidative stress. The aim of present study was to evaluate antioxidative strength and protective effects of drumstick (Moringa oleifera) leaf-water extract (DLWE) on kidney in Wistar rats. In this study rats were either fed with control diet or control diet with DLWE or high-fat diet or high-fat diet with DLWE for 16 weeks. The body and kidney weight, oxidative status (lipid peroxidation, ferric reducing antioxidant power, non-enzymatic and enzymatic antioxidants) and gene expression of superoxide dismutase and catalase were assessed. High fat-diet fed rats showed changes in body and kidney weights, increase in lipid peroxidation and decrease in ferric reducing antioxidant power, vitamin C, glutathione, superoxide dismutase and catalase indicating a higher oxidative stress index. At molecular level, high fat-diet caused a significant reduction in gene expression of superoxide dismutase and catalase which was overcome by DLWE supplementation. The oral supplementation of DLWE restored oxidative stress in high fat-diet fed rats. The diet restored lipid peroxidation and kidney antioxidants to control group level. It seems that DLWE has therapeutic potential, so be developed as a supplement to prevent obesity and related oxidative stress.